The Impact of Fiscal Policy on Economic Inflation Rates in Palestine, During the Period 1996-2017 - Mohamed hasen awad, Manel (Finance and Business Economies Review, 2022)
This study aimed to identify the impact of the evolution in the volume of both government expenditure and tax revenues on the economic inflation rates in Palestine. The study used the analytical descriptive method based on time series data 1996-2017 and the application of multiple regression technique to reach the real effect of these variables on economic inflation rates. The study has come to a range of results, of which, most importantly, was the significant effect of the financial policy on the inflation rates in the Palestinian territories represented by government expenditure, where the regression coefficient (0.01) with economic, The results also showed a positive and slow effect of one time period (one year), which is statistically significant at 10% of tax revenues on economic inflation rates in Palestine, Where the coefficient of regression (0.01) With a positive economic elasticity ( ...0 .) The study also recommended that the Palestinian National Authority should review the economic agreements with the occupation authority in order to re-crystallize new directions to enable them to control the tools of monetary policy as well as fiscal policy to be able to real treatment and control of the phenomenon of inflation